2021
DOI: 10.1016/j.ynstr.2021.100371
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression correlates of advanced epigenetic age and psychopathology in postmortem cortical tissue

Abstract: Psychiatric stress has been associated with accelerated epigenetic aging (i.e., when estimates of cellular age based on DNA methylation exceed chronological age) in both blood and brain tissue. Little is known about the downstream biological effects of accelerated epigenetic age on gene expression. In this study we examined associations between DNA methylation-derived estimates of cellular age that range from decelerated to accelerated relative to chronological age (“DNAm age residuals”) and transcriptome-wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 92 publications
(108 reference statements)
1
8
0
Order By: Relevance
“…We observed a significant decrease in expression for only a single gene, Rps27A ; however, this was not validated using qPCR. There remains debate as to whether the amygdala is a sexually dimorphic structure ( Marwha et al., 2017 ; Wolf et al., 2021 ; Chatzinakos et al., 2021 ; Montalvo-Ortiz et al., 2022 ). Evidence suggests there are intrinsic differences linked to sex hormones that may explain our sex-specific observations in the formation and expression of emotional memories ( Blume et al., 2017 ; Morris et al., 2008 ; Cooke and Woolley, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…We observed a significant decrease in expression for only a single gene, Rps27A ; however, this was not validated using qPCR. There remains debate as to whether the amygdala is a sexually dimorphic structure ( Marwha et al., 2017 ; Wolf et al., 2021 ; Chatzinakos et al., 2021 ; Montalvo-Ortiz et al., 2022 ). Evidence suggests there are intrinsic differences linked to sex hormones that may explain our sex-specific observations in the formation and expression of emotional memories ( Blume et al., 2017 ; Morris et al., 2008 ; Cooke and Woolley, 2005 ).…”
Section: Resultsmentioning
confidence: 99%
“…We also estimated DNAm age using two recently developed tissue‐specific algorithms that were developed for human brain (Choi et al, 2019) and human cortical tissue (Shireby et al, 2020). Details of DNA extraction, QC procedures, genotype and DNAm data cleaning and imputation, ancestry assignment and ancestral principal component (PC) estimation, DNAm cell type estimates, and DNAm age (Horvath DNAm age, Choi brain‐specific DNAm age, and Shireby cortical DNAm age) calculation are reviewed in the Supporting Information Materials and were previously described (Logue et al, 2021; Morrison, Miller, et al, 2019; Wolf et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The primary aim of this study was to examine associations between PTSD, MDD, and AUD and age‐adjusted transcriptomic age in three brain regions using data from the VA National PTSD Brain Bank (Friedman et al, 2017). We have previously studied this same cohort to test associations between psychopathology and advanced DNAm age (Wolf et al, 2021) and to evaluate the gene expression correlates of advanced DNAm age (Wolf et al, 2021). A second aim was to identify the genes and related biological processes that drive associations between PTSD, MDD, and/or AUD and age‐adjusted transcriptomic age and to evaluate associations between age‐adjusted transcriptomic age and estimates of specific neural cell type counts.…”
Section: Introductionmentioning
confidence: 99%
“…These mutations appeared to be linked to cytoskeletal and inflammation-related genes [48]. Finally, a post-mortem study of gene expression in the brains of veterans found four genes (SNORA73B, COL6A3, GCNT1 and GPRIN3) whose expression was associated with a lifetime diagnosis of PTSD [49].…”
Section: Genetic Epigenetic and Gene Expression-related Markersmentioning
confidence: 98%